Addiction and responsability : An inquiry into the addictive mind - Seeburger, Francis F. (The Crossroad Publishing Company, 1993)
Interest in the subject of addiction has grown remarkably in the last few decades. Popular literature on addiction hgas multiplied phenomenally.